MINERALOGY OF PYROXENITES AND APOPYROXENITE RODINGITES AND CHLORITOLITES OF THE KURTA ECLOGITE-SCHIST COMPLEX (UFALEY METAMORPHIC BLOCK, CENTRAL URALS) - А.I. Belkovsky (Минералогия)
Original data on mineralogy, petrography and ontogeny of garnet pyroxenites and products of their crustal metamorphism – rodingites, сhloritolites and talc-carbonate rocks from the Ufaley metamorphic block, Central Urals, are described at the paper.